Evaluation of citizen participation in World Bank projects in Algeria - Sidi Slimane District/Town of Bou Saada - Lemkhalti, Ahmed; Boudjemaa, Khalfallah (Technium Social Sciences Journal, 2022)
Citizen participation has become one of the pillars of good governance in order to achieve sustainable local development. This is what the World Bank’s contribution in Algeria has been aimed at, through the Precarious Habitat Resorption Program (P.H.R), by adopting the pattern of popular participation among its priorities to change the deteriorating situation experienced by the residents of these neighborhoods. This study is to assess the popular participation in these projects and to determine the extent to which they have affected public action and the improvement of the conditions of the population, and what obstacles have prevented the realization of the objectives of this; And as a research methodology, the descriptive method was used, as well as the method hqe2r, (h: high, q: quality, e: (environmental/ economic efficiency/social equity), r: (neighborhood renewal / building rehabilitation), through the L indi (indicateur’s Impact) application. The results of the first phase of the preliminary situational evaluation were evaluated at between 0 and 1.4, where a total absence of popular participation was noted. In the second phase of the evaluation, after the exploitation of the project, the indicators jumped to 3 points. This explains the significant improvement in public action, but popular participation remains below the required level, due to the weakness of the legal system and the absence of a legal framework that controls public action and restrains the authority of the administration